Analisis Regulasi Program Keluarga Harapan (PKH) dan Bantuan Pangan Non-Tunai (BPNT): Studi Kasus Dinas Sosial Kota Medan - Jhos Franklin Kemit (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This article examines the regulations for the Family Hope Program (PKH) and Non-Cash Food Assistance (BPNT) and their implementation in the Medan City Social Service. This research uses a normative method with a descriptive approach. The research results show that existing regulations have provided a clear framework for the implementation of PKH and BPNT, but there are still challenges in implementation. This case study identifies several obstacles and offers recommendations to improve program effectiveness.